2009
DOI: 10.1016/j.amjcard.2009.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Treating Children With Idiopathic Dilated Cardiomyopathy (from the Pediatric Cardiomyopathy Registry)

Abstract: In 40% of children with symptomatic idiopathic dilated cardiomyopathy (IDC), medical therapy fails within 2 years of diagnosis. Strong evidence-based therapies are not available for these children, and how evidence-based therapies for adults with IDC should be applied to children is unclear. Using data from the National Heart, Lung, and Blood Institute's Pediatric Cardiomyopathy Registry, we compared practice patterns of initial therapies for children with IDC diagnosed between 1990 and 1995 (n=350) and betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 19 publications
2
50
0
4
Order By: Relevance
“…A study of the epidemiologic characteristics of idiopathic CMP from the pediatric CMP registry in the USA revealed that approximately 5% of patients underwent cardiac transplantation, 2% IABP, 2% ECMO, and 1% VAD; however, the medical outcomes in these children did not show improvement in the previous several decades. 19 There have been reports on various therapeutic trials in addition to medical therapy of CMP prior to cardiac transplantation. 20- 22 Although we could not collect all of the data on CMP patients nationwide, the numbers of patients treated with surgical mechanical support have shown an increase in recent years and these therapeutic trials and experience might have an impact on the prognosis of primary CMP in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the epidemiologic characteristics of idiopathic CMP from the pediatric CMP registry in the USA revealed that approximately 5% of patients underwent cardiac transplantation, 2% IABP, 2% ECMO, and 1% VAD; however, the medical outcomes in these children did not show improvement in the previous several decades. 19 There have been reports on various therapeutic trials in addition to medical therapy of CMP prior to cardiac transplantation. 20- 22 Although we could not collect all of the data on CMP patients nationwide, the numbers of patients treated with surgical mechanical support have shown an increase in recent years and these therapeutic trials and experience might have an impact on the prognosis of primary CMP in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Many pediatric centersroutinely supplement their PDCM patients with carnitine [10,17], regardless of cause. This practice is contrary to American and European adult heart failure guidelines, in which routine use of nutritional, hormonal supplements, or both for the treatment of heart failure is not recommended [8,9]. The challenge for pediatric cardiologists treating PDCM is to ensure patients who truly will benefit from such therapy will be identified.…”
Section: Introductionmentioning
confidence: 95%
“…A number of these studies [46][47][48][49][50][51] have demonstrated short-term efficacy of ACE inhibitors for systemic ventricular dysfunction in children. It would appear that only approximately 65-70% of patients with an idiopathic dilated cardiomyopathy receive ACE inhibitors, and that proportion has remained stable from 1990 to 2006 [9]. ARBs have been studied in children with hypertension [52] but not heart failure.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[15] Left ventricular reverse remodeling (LVRR) appears to predict a lower rate of major cardiac adverse events independently from other factors, such as NYHA class or FMR. [12] It is mostly induced within the first 6 months of optimal medical treatment, [16] but can be completed at 24 months.…”
Section: Left Ventricular Reverse Remodeling: the Concept Of Dynamic mentioning
confidence: 99%